Ki-67 Expression is a Significant Prognostic Factor Only When Progesterone Receptor Expression is Low in Estrogen Receptor-Positive and HER2-Negative Early Breast Cancer. (28th December 2019) - Kang, Young-Joon; Lee, Han-Byoel; Kim, Yun Gyoung; Han, JaiHong; Kim, Yumi; Yoo, Tae-Kyung; Lee, Eun-Shin; Moon, Hyeong-Gon; Noh, Dong-Young; Han, Wonshik
Abstract : Objective . While the value of Ki-67 has been recognized in breast cancer, controversy also exists. The goal of this study is to show the prognostic value of Ki-67 according to progesterone receptor (PgR) expression in patients who have estrogen receptor- (ER-) positive, human epidermal growth factor receptor 2- (HER2-) negative early breast cancer. Methods . The records of nonmetastatic invasive breast cancer patients who underwent surgery at a single institution between 2009 and 2012 were reviewed. Primary end point was recurrence-free survival (RFS), and secondary end point was overall survival (OS). Ki-67 and PgR were assessed with immunohistochemistry for the tumor after surgery. Results . A total of 1848 patients were enrolled in this study. 223 (12%) patients had high (≥10%) Ki-67, and 1625 (88%) had low Ki-67 expression. Significantly worse RFS and OS were observed in the high vs. low Ki-67 expression only when the PgR was low (<20%) (p < 0.001 and 0.005, respectively, for RFS and OS). There was no significant difference in RFS and OS according to Ki-67 when the PgR was high (p = 0.120 and 0.076). RFS of four groups according to high/low Ki-67 and PgR expression was compared. The low PgR and high Ki-67 expression group showed worst outcome among them (p < 0.001 ). In a multivariate analysis, high Ki-67 was an independent prognostic factor when the PgR was low (HR 3.05; 95% CI 1.50–6.19; p = 0.002 ). Conclusions . Ki-67 had a value as a prognostic factor only under low PgR expression level in early breast cancer. PgR should be considered in evaluating the prognosis of breast cancer patients using Ki-67.